Design and Construction of an Electronic Mosquito Repellant. - Kwesiga, Isaac (Kabale University, 2023)
This work is titled design and construction of an electronic mosquito repellant device Mosquito repellants like coils, mats, liquid vaporizers and creams are often used at various places. However, they are prone to be fatal and can cause harm to human beings. For instance, mosquito repellant creams and creams can cause adverse effects on the skin like allergic reactions. Coils, mats can produce toxic fumes when heated and cause breathing trouble whereas liquid vaporizers can also produce fumes when heated. For efficient result without any side effects, the most optimum solution is constructing a simple electronic device with minimal components which can produce output so as to repel the mosquitoes. The aim of this work is to design an a simple electronic device which can produce ultrasound in the frequency range of 20kHz to 38kHz, which can scare away mosquitoes. Keywords: Design Construction, Electronic Mosquito Repellant.